RESULTS OF GENDER ANALYSIS OF ENGINEERING UNIVERSITY EDUCATIONAL PROCESS - Natalya Alexandrovna Sukhorukova (Advanced Engineering Research)
The results of the gender analysis of the educational process in the engineering university are presented. The gender analysis is made in stages, and it is defined by the well-structured diagram. Within the frame of this research, the gender analysis appears a constituent of the gender strategy of the engineering university. It serves to discover the gender sensitivity level of the main components of the educational process. The gender strategy of the university is proved, and it is considered as a practical mechanism for the implementation of ideas and principles of the gender approach in the educational practice of the universities. The author has elaborated the gender sensitivity rating scale of the university educational process, and has worked out the criteria to be considered while conducting the gender analysis. Interactions of the educational process parties, the training material content, research interests of male and female students, methods and practices systems of the youth outreach are studied in this context. As a result, a number of significant gender problems of the educational process in the engineering university — in particular, a low level of the gender sensitivity of the above-mentioned subjects of research — are discovered.